Respuesta :

Answer:

-16

Step-by-step explanation:

We are given the expression:

-c+6x

and asked to evaluate when c=4 and x=-2. Therefore, we must substitute 4 in for c and -2 in for x.

-(4)+6(-2)

Solve according to PEMDAS: Parentheses, Exponents, Multiplication, Addition, Subtraction.

First, multiply 6 and -2.

6 * -2= -12

-(4)+ -12

-(4) -12

Distribute the negative sign.

-4 -12

Subtract 12 from -4.

-16

The expression -c+6x when c=4 and x= -2 is -16.

Answer:

-16

Step-by-step explanation:

Start with -C+ 6x.  Replace C with '4' and x with '-2'

This comes out to -(4) + 6(-2) = -4 - 12 = - 16